REVITALIZATION AND ACTUALIZATION OF THE NON-ALIGNED MOVEMENT IN INTERNATIONAL POLITICAL DYNAMICS - BediBudiman; ObsatarSinaga; Yanyan M. Yani; TaufikHidayat (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The relevance of the spirit and values ??regarding peace, sovereignty and solidarity for development that can be implemented concretely through concrete steps will further strengthen the existence of the Non-Aligned Movement (NAM) organization. The role of NAM in facing the current unipolar international political situation is increasingly needed amidst the increasingly intensive meaning and revitalization of global partnerships between developed and developing countries to strengthen the spirit of multilateralism.Multilateralism must remain the foundation of international cooperation, in the midst of various global challenges such as the economic crisis, the growing number of refugees, the threat of terrorism and radicalism, as well as conflicts between countries, including among NAM members, will continue to overshadow the international realm with an increasingly crucial and complex form. That is why, the NAM countries must continue to strengthen political solidarity between members through tighter and more solid cooperation in order to further strengthen global partnerships for developing countries.